The stock market effects of committing and setting GHG targets: Evidence from the science-based initiative - Santiago Guerrero-Escobar; Gerardo Hernández del Valle; Marco Hernández Vega; Paula de la Mora (Banco de México, 2023)
Many companies are setting ambitious targets to reduce their greenhouse gas emissions (GHG) per the Paris Agreement. However, there is limited evidence on the market effects of setting those targets. Using a GARCH model with a trend developed by the authors and a panel fixed effects model, this paper analyzes the short-run effects of committing and setting GHG targets on public companies' stock price returns and volatility. We find no evidence that committing or setting a target yields higher returns but contributes to a reduction in price volatility, albeit the impact is short-lived. In view of these results, we conclude that there are no visible stock market gains in the short term for companies that commit and set GHG targets and that other factors may explain their motivations to engage in GHG mitigation actions.
Keywords: C1; E1; I0; O4; 330; Stock returns; Volatility; GHG emissions; ESG; GARCH